IMPLEMENTATION OF IMPROVING ENGLISH LANGUAGE ABILITY WITH KHODAM (KOGNITIF, DEMONSTRATIF, MANDIRI) BASED ON INFORMATION TECHNOLOGY - Munfadlila, Asef Wildan; Perdana, Andi (Suluh Adiluhung Publisher (SAPub), 2025)
In the current era of globalization, English language proficiency is a critical requirement, particularly for individuals who aspire to enhance their competitiveness in the job market or education sector. Nevertheless, numerous individuals continue to encounter challenges in obtaining the necessary resources to effectively acquire the English language. The objective of this community service activity is to enhance multimedia-based English skills by providing innovative, interactive, and intensive training. This program is intended to establish an engaging and accessible learning environment by incorporating multimedia technology, including interactive videos, computer-based simulations, and learning applications. An introduction to multimedia tools, ongoing mentoring, and direct training sessions comprise the implementation method. The activity is intended for the general public, which includes students, laborers, and housewives, who require assistance in enhancing their English communication abilities. The improvement of participants' abilities is assessed through initial and concluding tests. As well as participants' motivation to learn, the outcomes of the activity demonstrated substantial enhancements in their English listening, speaking, reading, and writing abilities. Consequently, this program significantly enhances the English language proficiency of the community by employing a multimedia-based methodology.